The psychology of buddhism in conflict studies - Silva, Padmasiri (Springer, 2020)
This book provides an interdisciplinary discussion of conflict studies, drawing on perspectives from psychology and Buddhist studies. The author combines current research in psychology, conflict and management studies, as well as moral narratives drawn from religious and cultural contexts, to offer useful guidance on dealing with conflict and dichotomies. Drawing on a vast corpus of Buddhist literature, this book examines complex teachings, ideas and doctrines to bring insight to how individuals and societies might lead peaceful and balanced lifestyles. In this ground-breaking study Padmasiri De Silva insists that the social studies need to develop dialectical methods and understanding in addition to the objective and analytical collection of facts. Chapters cover an array of subjects including economics, ecology, human wellbeing, prison reform, dialectical behaviour therapy, multiculturalism, and peace studies.Preface.- Chapter 1 Introduction.- Chapter 2 The Buddhist Critique of Metaphysical Entanglements.- Chapter 3 The Many Faceted Nature of a Crisis.- Chapter 4 The Psychological Dimensions of Conflict and Harmony.- Chapter 5 Criminal Justice through a Buddhist Contemplative Path.- Chapter 6 Exploring Multiculturalism.- Chapter 7 Dilemmas, Conflicts and Paradoxes in Management Studies.- Chapter 8 Erosion of Moral Values in an Era of Market Triumphalism.- Chapter 9 Conflict and Peace Studies.- Chapter 10 Idea of the Self: the Narrow Ridge between the paths of chaos and nihilism and the Traps of Identity Illusions.- Chapter 11 Dialectical Behaviour Therapy.- Chapter 12 Resolving Paradoxes in Tibetan Buddhism and Zen Buddhism.- Chapter 13 Emotions, Logic and Rationality.